A Morphological Characterization of High Yield Chitin from Periwinkle Shells - Odili, Cletus Chiosa; Gbenebor, Oluwashina Philips; Henry Adekola Haffner,; Samson Oluropo Adeosun, (Journal of Casting & Materials Engineering, 2020)
Research on obtaining chitin from periwinkle shell is scarce due to the very low yield of chitin from this kind of shell. Thisstudy reports a method of processing periwinkle shells to obtain high yield, bio-medically suitable chitin. The experimentwas designed using IM and 2M concentrations of HCl for demineralization and a 1M NaOH concentration for deproteinization. FTIR, SEM, XRD and DTA analytical tools were used to characterize the extracted chitin. The FTIR spectral, XRD patterns and SEM analysis, revealed the complete removal of calcium carbonate by the acid concentrations used. The particle-like form of periwinkle shell was transformed to sheet-like fiber and globular-like fiber of α-chitin by increasing the concentration of HCl from1M to 2M respectively. The crystal size increased from 11.2Å (1M HCl) to 13.4Å (2M HCl). The yield of chitin from periwinkle shell also increased from 52% to 71% using 1M and 2M HCl respectively. Thus, acid concentrations can be used to alter the structure of chitin with different mechanical properties.